Vulnerability of the unbanked: evidence from a developing country. (17th March 2016) - Kamran, Sohail; Uusitalo, Outi
Abstract: Financial exclusion is an apparent phenomenon globally, the majority of people without bank accounts living in the developing countries. Those who lack access to financial services could experience vulnerability. Therefore, the purpose of this study was to unfold the vulnerability of the low‐income unbanked consumers in a Pakistani context. Qualitative data were gathered from low‐income unbanked consumers through in‐depth interviews. The findings suggest that unbanked consumers are vulnerable in many ways. The participants faced several negative consequences due to their financial exclusion, which resulted into their personal, economic and social detriment. Based on our study findings, we provide managerial and public policy implications for the well‐being of the low‐income unbanked consumers. Lastly, study limitations and future study guidelines are discussed.